2017
DOI: 10.14283/jpad.2017.44
|View full text |Cite
|
Sign up to set email alerts
|

The Value of Pre-Screening in the Alzheimer’s Prevention Initiative (Api) Autosomal Dominant Alzheimer’s Disease Trial

Abstract: The Alzheimer’s Prevention Initiative (API) Autosomal Dominant Alzheimer’s Disease (ADAD) trial evaluates the anti-amyloid-β antibody crenezumab in cognitively unimpaired persons who, based on genetic background and age, are at high imminent risk of clinical progression, and provides a powerful test of the amyloid hypothesis. The Neurosciences Group of Antioquia implemented a pre-screening process with the goals of decreasing screen failures and identifying participants most likely to adhere to trial requirem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Our sample included more females overall, and more female PSEN1 mutation carriers. This is possibly a recruitment bias, as previously documented, 63 whereby males were more likely to fail pre‐screening requirements, particularly due to substance abuse. Moreover, female PSEN1 mutation carriers were younger (1.8 years) than male PSEN1 mutation carriers.…”
Section: Discussionmentioning
confidence: 77%
“…Our sample included more females overall, and more female PSEN1 mutation carriers. This is possibly a recruitment bias, as previously documented, 63 whereby males were more likely to fail pre‐screening requirements, particularly due to substance abuse. Moreover, female PSEN1 mutation carriers were younger (1.8 years) than male PSEN1 mutation carriers.…”
Section: Discussionmentioning
confidence: 77%
“…Finally, economic constraints [ 72 ] and opportunity costs in the form of lost wages, coupled with lack of any financial compensation for their time [ 67 ] may also negatively impact recruitment efforts. A recent analysis by Rios-Romenets and colleagues [ 74 ] suggests nearly half of prospective, high-risk participants decline participation, largely due to factors related to study burden, including the protocol itself, as well as travel and work burden.…”
Section: Participant Burdenmentioning
confidence: 99%
“…Previous research into barriers to clinical trial participation found that economic, structural, and logistical obstacles negatively impacted recruitment efforts, with examples including financial burdens, time constraints, and transportation inconveniences (Bonk, 2010; Clark et al, 2019; Clement et al, 2019; Cox et al, 2019; Graham et al, 2017; Heller et al, 2014; Indorewalla et al, 2021; Jefferson et al, 2011; Largent et al, 2018; McDougall et al, 2015; Rios-Romenets et al, 2018; Vaswani et al, 2020; Young et al, 2015). A lack of participation from key groups within the US population affects the generalizability of trial results, effectiveness of therapeutic agents, and equity in the provision of health care (Coakley et al, 2012; George et al, 2014; Indorewalla et al, 2021; Kwiatkowski et al, 2013; Rivers et al, 2013; Swanson and Bailar, 2002).…”
mentioning
confidence: 99%
“…Even when individuals were interested in participating in clinical trials for altruistic or personal reasons, they referenced similar logistical, financial, and psychosocial barriers that dissuaded them from enrolling (Cox et al, 2019; Jefferson et al, 2011). Such barriers were often cited as including, but not limited to, opportunity costs in the form of lost wages, lack of financial compensation for their time, potential health risks, lack of adequate transportation, prolonged study durations, and lack of access to health insurance (Bonk, 2010; Clark et al, 2019; Clement et al, 2019; Cox et al, 2019; Graham et al, 2017; Heller et al, 2014; Indorewalla et al, 2021; Jefferson et al, 2011; Largent et al, 2018; McDougall et al, 2015; Rios-Romenets et al, 2018; Vaswani et al, 2020; Young et al, 2015). These impediments to clinical trial enrollment are especially important for diseases like AD, which has ethnicity-dependent pathophysiology, thereby indicating the importance of diversity in clinical trial participation (Howell et al, 2017; Morris et al, 2019).…”
mentioning
confidence: 99%